2019
DOI: 10.1186/s12943-019-1109-9
|View full text |Cite
|
Sign up to set email alerts
|

Functions of N6-methyladenosine and its role in cancer

Abstract: N6-methyladenosine (m6A) is methylation that occurs in the N6-position of adenosine, which is the most prevalent internal modification on eukaryotic mRNA. Accumulating evidence suggests that m6A modulates gene expression, thereby regulating cellular processes ranging from cell self-renewal, differentiation, invasion and apoptosis. M6A is installed by m6A methyltransferases, removed by m6A demethylases and recognized by reader proteins, which regulate of RNA metabolism including translation, splicing, export, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
927
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 967 publications
(940 citation statements)
references
References 168 publications
(210 reference statements)
13
927
0
Order By: Relevance
“…Recent studies have shown that m 6 A modification in mRNAs participates in RNA metabolisms to regulate mRNA stability, splicing, transport, localization, as well as in stem cell self-renewal and differentiation, tissue development in normal cellular physiological and disease status [10,[17][18][19]. Recent studies have reported that the writers, readers, and erasers of m 6 A may play important roles in various cancer initiation, progression and response to immunotherapy via different regulation patterns [18,[20][21][22][23][24]. Despite these recent discoveries between m 6 A modification with malignant cancer development and treatment, the status of m 6 A modification and the underlying regulatory mechanism in CRC, especially in the glycolytic metabolism of CRC remains little known.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that m 6 A modification in mRNAs participates in RNA metabolisms to regulate mRNA stability, splicing, transport, localization, as well as in stem cell self-renewal and differentiation, tissue development in normal cellular physiological and disease status [10,[17][18][19]. Recent studies have reported that the writers, readers, and erasers of m 6 A may play important roles in various cancer initiation, progression and response to immunotherapy via different regulation patterns [18,[20][21][22][23][24]. Despite these recent discoveries between m 6 A modification with malignant cancer development and treatment, the status of m 6 A modification and the underlying regulatory mechanism in CRC, especially in the glycolytic metabolism of CRC remains little known.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence shows that the methylation of m6A mRNA is closely related to the occurrence and development of tumors. The expression level of m6Arelated protein is an important regulatory factor that directly determines the pathological process of tumor development [6]. However, the m6A modi cation in the regulation of EOC is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…RNA methylation can reverse the methylation modi cation at the RNA level, which is an extremely important epigenetic modi cation [4]. Further, 6-methyladenine (m6A) is the most abundant methylation modi cation of mRNA in eukaryotic cells, involving the participation of three types of molecules: methyltransferase complex (METTL3, METTL14, and WTAP), named as "Writers"; demethylase (FTO and ALKBH5), named as "Erasers"; and m6A-modi ed binding protein (YTHDF1/2/3), named as "readers", which can dynamically and reversibly regulate the m6A level [5,6]. In 2017, Professor Chuan's research team found that m6A was involved in the regulation of self-renewal and differentiation of glioblastoma stem cells (GSCs).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another study also demonstrates the overexpression of METTL3 can dramatically suppress proliferation, migration and invasion for colorectal carcinoma (CRC) cells [25]. Thus, m6A regulator genes are not only promising to become the potential molecular markers for cancer diagnosis and prognosis, but also quali ed to serve as the targets for the design of targeted anticancer drugs, which has been demonstrated in several literatures [26][27][28]. Several studies have investigated the role of m6A regulator genes in the survival of cancers, such as glioma [29], gastric cancer [30], and head and neck squamous cell carcinoma [31].…”
Section: Introductionmentioning
confidence: 92%